Startschuss für die digitale Zukunft - Das Digital Talents Program geht in die nächste Runde - Kundisch, Dennis

Zahlenmuster und Brüche: Eine Lernumgebung zum algebraischen Denken - Rezat, Sebastian; Doligkeit, Nadja (mathematik lehren)

In vacuum metasurface for optical microtrap array - Li, Donghao; Liao, Qiming; Xu, Beining; Zentgraf, Thomas; Narvaez Castaneda, Emmanuel; Zhou, Yaoting; Qin, Keyu; Xu, Zhongxiao; Shen, Heng; Huang, Lingling (Optics Express)
Optical tweezer arrays of laser-cooled and individually controlled particles have revolutionized atomic, molecular, and optical physics. They afford exquisite capabilities for applications in quantum simulation of many-body physics, quantum computation, and sensing. Underlying this development is the technical maturity of generating scalable optical beams, enabled by active components and a high numerical aperture objective. However, such a complex combination of bulk optics outside the vacuum chamber is very sensitive to any vibration and drift. Here, we demonstrate the generation of a 3 × 3 static tweezer array with a single chip-scale multifunctional metasurface element in vacuum, replacing the meter-long free space optics. Fluorescence counts on the camera validate the successful trapping of the atomic ensemble array and showcase a promising strategy for integrated photonics with cold atom systems. The introduction of a polarization independent dual-wavelength metasurface significantly enhances fluorescence collection efficiency while reducing experimental complexity. This approach paves the way for scalable neutral atom platforms and offers a compelling route towards the realization of next generation quantum metasurfaces.

Christoph Haar (Hg.): Slavery, Law and Religion in the Early Modern Period (Law and Religion in the Early Modern Period/ Recht und Religion in der Frühen Neuzeit. 7). Leiden, Boston 2024 - Priesching, Nicole (Theologische Revue)

Berichtete Praktiken der Lernbegleitung bei der Förderung von arithmetischen Basiskompetenzen - Neufeld, Inga (Was ist wichtig? Perspektiven auf den Mathematikunterricht der Grundschule)

Antonio Negri, Spinoza, Marx, and Digital Capitalism. - Fuchs, Christian (Philosophy and Social Criticism)

Technikrecht - Ensthaler, Jürgen; Gesmann-Nuissl, Dagmar; Müller, Stefan

A Measurement Setup for the Determination of Temperature-Dependent Viscoelastic Material Parameters Using an Ultrasonic Pulse-Echo Technique - Dreiling, Dmitrij; Itner, Dominik; Gravenkamp, Hauke; Birk, Carolin; Henning, Bernd (2025 International Congress on Ultrasonics)

Explanation needs and ethical demands: unpacking the instrumental value of XAI - Alpsancar, Suzana; Buhl, Heike M.; Matzner, Tobias; Scharlau, Ingrid (AI and Ethics)

Explainability and AI Governance - Reijers, Wessel; Matzner, Tobias; Alpsancar, Suzana (Digital Development. Technology, Ethics and Governance)

Monitoring the curing process of adhesive bonds using selective excitation of guided ultrasonic waves - Zeipert, Henning; Nellius, Tom; Schönlau, Nikolas; Wippermann, Mareen; Claes, Leander; Nicolai, Marcel; Prager, Jens; Henning, Bernd (2025 International Congress on Ultrasonics)

The structure of the double discriminant - Anderson, Theresa C.; Asarhasa, Ufuoma V.; Bertelli, Adam; Gundlach, Fabian; O'Dorney, Evan M. (arXiv:2507.16138)
For a polynomial $f(x) = \sum_{i=0}^n a_i x^i$, we study the double discriminant $DD_{n,k} = \operatorname{disc}_{a_k} \operatorname{disc}_x f(x)$. This object has been well studied in algebraic geometry, but has been brought to recent prominence in number theory by its key role in the proof of the Bhargava--van der Waerden theorem. We bridge the knowledge gap for this object by proving an explicit factorization: $DD_{n,k}$ is the product of a square, a cube, and possibly a linear monomial. Our proof is entirely algebraic. We also investigate other aspects of this factorization.

"Himmel" und "Hölle" als Sinnbilder der Seele - Garske, Volker

Forward-Biased Silicon Phase Shifter Modeling for Electronic-Photonic Co-Simulation and Validation in a 250 nm EPIC BiCMOS Technology - Schwabe, Tobias; Kress, Christian; Kruse, Stephan; Weizel, Maxim; Rhee, Hanjo; Scheytt, J. Christoph (Journal of Lightwave Technology)
Keywords: Integrated circuit modeling; Capacitance; Silicon; Modulation; Adaptation models; Semiconductor device modeling; Bandwidth; Data communication; electrooptical transmitter; equalization; free-carrier-plasma dispersion effect; modelling; optical modulator; phase shifter; silicon photonics

A Photonic Assisted Visible Light FMCW Lidar System for Large Aperture Phased Array MIMO Based on LEDs - Kruse, Stephan; Brockmeier, Jan; Schwengelbeck, Max; Schwabe, Tobias; Scheytt, J. Christoph (2025 55th European Microwave Conference (EuMC))
Keywords: Phased arrays; Optical fibers; Optical fiber sensors; Laser radar; Optical variables measurement; Apertures; Light emitting diodes; Optical receivers; Optical transmitters; Optical modulation; Lidar; light detection and ranging; FMCW; frequency modulated contentious wave; visible light sensing (VLS); visible light communication (VLC); automotive headlights; light emitting diode (LED); microwave photonics; wireless sensing

Analysis and Design of Forward Biased Silicon Photonics Phase Shifter Equalizer Circuits - Schwabe, Tobias; Kress, Christian; Sadiye, Babak; Kruse, Stephan; Scheytt, J. Christoph (IEEE Access)
Keywords: Optical attenuators; Equalizers; Phase shifters; Optical modulation; Electro-optic modulators; Optical amplifiers; Circuits; Silicon photonics; Optical saturation; Integrated circuit modeling; Data communication; equalization; electro-optical transmitter; silicon photonics; phase shifter; optical modulator; free-carrier plasma dispersion effect; driver architectures; biasing schemes

Electrooptical Integration of an Electronic Photonic Integrated Circuit Into Plastic Substrates Using Mid-Technology - Kruse, Stephan; Diri, Jabil; Mager, Thomas; Kress, Christian; Scheytt, J. Christoph (2025 55th European Microwave Conference (EuMC))
Keywords: Optical fibers; Integrated optics; Semiconductor device measurement; Laser radar; Optical device fabrication; Photonic integrated circuits; Microwave theory and techniques; Optical fiber devices; Plastics; Substrates; Microwave photonics; photonic radar; optical LO distribution; mechatronic integrated device (MID)

Antennenvorrichtung zum Aussenden von elektromagnetischer Strahlung für ein Kraftfahrzeug sowie Kraftfahrzeug - Kruse, Stephan; Meinecke, Marc-Michael; Gisder, Thomas; Simoni, Renato; González-Huici, Maria Antonia; Greiff, Christian; Mateos-Nunez, David; Danklmayer, Andreas; Ladan, Julien; Kurz, Heiko Gustav

Optisch basierter Digital-Analog-Umsetzer - Kruse, Stephan; Silberhorn, Christine; Brecht, Benjamin; Schwabe, Tobias

Unpacking Hostile Attitudes towards Islam and Muslims: A Differentiated Approach to Understanding Perceptions of Religion and People - Diekmann, Isabell (Patterns of Prejudice)
Anti-Islam and anti-Muslim attitudes are frequently perceived without sufficient differentiation. The absence of a clear distinction between attitudes towards individuals and attitudes towards the religion itself is evident in definitions that conflate (attitudes towards) Islam and Muslims, as well as in the operationalization process where surveys on overtly anti-Muslim attitudes are labelled as measuring anti-Islam attitudes. To explore whether the interchangeable usage of these terms is valid or whether there is empirical evidence supporting the need to differentiate between anti-Islam and anti-Muslim attitudes, an online survey was conducted (n = 497). The results indicate that anti-Islam and anti- Muslim attitudes are statistically distinct constructs that are nevertheless correlated. Furthermore, the study investigates the extent to which variations in the degree of hostile attitudes towards Islam and Muslims can be observed. The findings reveal that Islam is evaluated significantly more negatively than Muslims. In addition, an analysis of free associations related to the terms Islam and Muslims highlights notable differences. Although the respondents oftentimes see Muslims in the context of migration and integration, associations with Muslims tend to be more positive and based on personal experiences and interactions than associations with Islam. Associations with Islam, on the other hand, are characterized by threat and conflict and externalization to foreign countries. These findings have important implications for the theoretical conceptualization of anti- Islam and anti-Muslim attitudes. By differentiating between anti-Islam and anti- Muslim attitudes, it becomes possible to deconstruct these phenomena into their constituent elements and to understand their various dimensions. It is only through such disentanglement that the interconnected nature of anti-Islam and anti-Muslim attitudes can be comprehensively examined and effectively addressed.